The pyrrolizidine alkaloids : studies on the pyrrolizidine base Retronecanol - Welgemoed, Jacobus Cornelius (Department of Chemistry, 2016)
Degradative and biosynthetic studies were performed on retronecanol1 obtained from monocrotaline, the alkaloid present in Crotalaria spectabilis. Previously two different theories regarding the biosynthesis of the pyrrolizidine bases had been proposed. Conflicting results in this school emphasised the need for a critical examination of the degradative procedure. Heliotridane, derived from retronecanol, was submitted to the Hofmann degradation. The product of the reaction was shown by gas-liquid chromatography to be a mixture with at least five components. Attempts to separate and purify the components were unsuccessful, although some information regarding their identity was deduced. The mass spectra of retronecanol, heliotridane and heliotridene were obtained and plausible rationalisations of these spectra are presented. In order to circumvent the difficulties previously encountered in the degradation, attempts were made to obtain retronecanone from retronecanol by oxidation on a small scale. Three different oxidants, however, failed to give the required product. Plants of Crotalaria spectabilis were fed with [5-¹⁴C]-ornithine, followed by degradation of the active monocrotaline 1 obtained to give the activities of carbon atoms 1 and 1' of the pyrrolizidine base. The results are consistent with a theory which invokes a symmetrical intermediate in the biogenesis of ring B of the pyrrolizidine unit.